Do lower interest rates boost consumption? : An insight into low-interest rate environments and consumption behavior in Germany. - Oviedo Arevalo, Daniel Camilo; Slaný, Martin, 1982-; Mach, Petr, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
During the period 2010 – 2019, the monetary landscape for many countries evolved around low-interest rate environments. These environments, during which interest rates close to zero or lower were sustained for several years, had an impact that is still to be evaluated, especially when it refers to household consumption. To test the hypothesis that low-interest rate environments do boost consumption even during prolonged periods of time, information of the last decade on several indicators related to consumption in Germany was collected (Interest Rates, GDP, Disposable Income, Consumer Price Indices, Unemployment rate and Consumer Confidence Inex). A theory-driven regression model was developed, and the results proved the existence of a negative relationship between interest rates and household consumption.
Vedoucí práce: Martin Slaný
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses